Pole climbing robot for connecting distribution lines - Khalid, Zahra Bakhiar; Ahmed, Razu; Kaish, Imrul; Ullah, Md. Hasib (BRAC University, 2015)
This thesis report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Electrical and Electronic Engineering, 2015.